Implementasi Pendekatan Gamifikasi untuk Meningkatkan Kreativitas Mahasiswa PGSD dalam Merancang Media Pembelajaran Sekolah Dasar - Meilani Tirta Sari; Aswasulasikin Aswasulasikin; Mazda Leva Okta Safitri; Bunda Harini; Nurdin Kamil; Ilham Arya Susanto (Educatio, 2026)
This study aims to analyze the implementation of a gamification approach in the Learning Media and Technology course and its effect on the creativity of Primary School Teacher Education (PGSD) students at Universitas Sriwijaya in designing learning media for elementary school students. This study employed a pre-experimental method with a One-Group Pretest-Posttest design, involving 32 PGSD students who received a gamification intervention over six meetings, incorporating elements such as points, badges, leaderboards, and tiered challenges. Creativity data were collected through a product assessment rubric based on four indicators, namely fluency, flexibility, originality, and elaboration, which were then analyzed using a paired sample t-test, N-Gain Score, and Cohen's d. The results showed that students' average creativity scores increased significantly from 58.75 in the pretest to 87.41 in the posttest (t = 20.68; p = 0.000), with an N-Gain of 0.695 (moderate to high category) and a Cohen's d of 3.67, categorized as a very large effect. The originality indicator, despite being the weakest at pretest, recorded the highest increase among all indicators. It is concluded that the gamification approach is effective when applied in the Learning Media and Technology course to enhance the creativity of PGSD students as prospective elementary school teachers. Keywords: creativity, elementary school learning media, gamification, PGSD students